Disruptive Technologies in the Credit Information Sharing Industry : Developments and Implications - World Bank Group (World Bank, Washington, DC, 2019)
This note analyzes the evolution of Credit Information Systems, including the emergence of new technologies that use alternative data in credit decisioning and the opportunities and risks associated with these trends. This paper also predicts the potential development effect of these disruptive technologies and proposes a role for the World Bank Group in leveraging these technologies to promote inclusion and stability.